Hydrogen Peroxide and Polyamines Act as Double Edged Swords in Plant Abiotic Stress Responses - Gupta, Kamala; Sengupta, Atreyee; Chakraborty, Mayukh; Gupta, Bhaskar (Frontiers in Plant Science, 2016)
The specific genetic changes through which plants adapt to the multitude of environmental stresses are possible because of the molecular regulations in the system. These intricate regulatory mechanisms once unveiled will surely raise interesting questions. Polyamines and hydrogen peroxide have been suggested to be important signalling molecules during biotic and abiotic stresses. Hydrogen peroxide plays a versatile role from orchestrating physiological processes to stress response. It helps to achieve acclimatization and tolerance to stress by coordinating intra-cellular and systemic signalling systems. Polyamines, on the other hand, are low molecular weight polycationic aliphatic amines, which have been implicated in various stress responses. It is quite interesting to note that both hydrogen peroxide and polyamines have a fine line of inter-relation between them since the catabolic pathways of the latter releases hydrogen peroxide. In this review we have tried to illustrate the roles and their multifaceted functions of these two important signalling molecules based on current literature. This review also highlights the fact that over accumulation of hydrogen peroxide and polyamines can be detrimental for plant cells leading to toxicity and pre-mature cell death.